Objective and subjective parameters of oral health in South Indian children: A cross-sectional study - P R Geetha Priya; Sharath Asokan; D Kandaswamy (Wolters Kluwer Medknow Publications, 2018)
Background: Oral health of schoolchildren is a strong predictor of their overall well-being. This study was planned to assess and compare the objective and subjective parameters of oral health of South Indian school children. Methodology: Three hundred and sixty school children participated in this cross-sectional study. Their oral hygiene status, dental caries status, and treatment needs were assessed. Two questionnaires were filled by these children, to assess their oral health-related quality of life (OHRQoL) and their knowledge on oral health. Their academic scores were collected from the schools. Statistical analysis was done using Kruskal-Wallis ANOVA test and Spearman correlation test appropriately. Results: Children with no caries had better OHRQoL (P = 0.02). There was a negative correlation between dental caries status and OHRQoL score (P = 0.003) and dental caries treatment needs and OHRQoL score (P = 0.01). There was a positive correlation between knowledge on oral health and OHRQoL score (P = 0.02). Conclusion: Children with no caries had a better OHRQoL when compared to children with caries. Children with caries had more treatment needs, poor oral hygiene, low quality of life, and performed lesser in academics. However, they had adequate knowledge on oral health. Hence, both objective and subjective parameters of oral health should be given importance while treating children.